Physical Appearance Perfectionism: Psychometric Properties and Factor Structure of an Assessment Instrument in a Representative Sample of Males - Rica, Robin; Solar, María; Moreno-Encinas, Alba; Foguet, Sara; Compte, Emilio Juan; Sepúlveda, Ana Rosa (Frontiers in Psychology, 2022)
Perfectionism is a multidimensional construct with both positive and negative aspects. Recently, the concept of appearance-oriented perfectionism has been introduced, which is associated with body image dissatisfaction and weight and shape control behaviors. The Physical Appearance Perfectionism Scale (PAPS) is a 12-item two-factor instrument developed to assess this new dimension of perfectionism. The aim of the study is to validate the Spanish version of PAPS among a representative sample of 850 male university students in Spain (M = 20 years old; SD = 2.7). Exploratory and confirmatory factorial structure, internal consistency, convergent and concurrent validity, and associated predictor variables analyses have been carried out. Results showed that the Spanish version of the PAPS maintains the original factor structure with all items and proves to be a reliable instrument. Physical appearance-oriented perfectionism is associated with general perfectionism, higher body dissatisfaction, Eating Disorders and Muscle Dysmorphia symptomatology, and compulsive exercise, particularly in the Worry about Imperfection subscale. These variables also act as predictors of physical appearance perfectionism. The use of the PAPS-S and the analysis of its subscales is recommended in the context of body image-related pathologies such as Eating Disorders and Muscle Dysmorphia.